KONTRIBUSI PENDUDUKAN JEPANG BAGI PERSATUAN UMAT ISLAM DI INDONESIA - St. Khadijah (Hunafa: Jurnal Studia Islamika, 2007)
Japanese occupation in Indonesia has made Indonesia not only disadvantagous but also advantaggous country. Because of Japanese imperialism to Indonesia. Indonesia experienced  economic sufferings. However, Japanese political policy was very helpful to the unity of Indonesian Muslim under Islamic Organization, Masyumi (The Syurah Council of Indonesian Muslim). It was in this Islamic organization that Indonesian Muslim had the opportunity of consolidating their political strategy to expel Japanese from Indonesia. Kata Kunci: Pendudukan Jepang, Persatuan Umat Islam